Ultrahigh-anisotropy heat-conducting MXene film and preparation method thereof

Through alternating layer-layer self-assembly method and interface cross-linking technology, MXene/MMT composite films were prepared, which solved the problem of insufficient performance of existing thermal conductive films, achieved high-performance anisotropic thermal conductivity, and provided a better cooling solution for high-performance electronic devices.

CN119795691APending Publication Date: 2025-04-11BEIHANG UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411986329.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The performance of existing anisotropic thermally conductive films is lower than required and it is difficult to effectively apply in high-performance electronic devices.

Method used

The MXene/MMT alternating layered structure was designed and prepared by alternating layer self-assembly method, and an alternating stacking of Ti3C2Tx MXene nanosheets and montmorillonite nanosheets were used, and the interface interaction was enhanced by the introduction of silane coupling agent to prepare ultra-high anisotropic thermal conductivity MXene films.

Benefits of technology

It achieves ultra-high anisotropic thermal conductivity, high in-plane thermal conductivity, low out-of-plane thermal conductivity, and anisotropy index of 259~707, which has better cooling efficiency than traditional commercial thermal conductivity films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119795691A_ABST
    Figure CN119795691A_ABST
Patent Text Reader

Abstract

The invention relates to a heat-conducting MXene film with ultrahigh anisotropy and a preparation method of the heat-conducting MXene film. The ultrahigh-anisotropy heat-conducting MXene film is an MXene / MMT composite film and is formed by alternately stacking a plurality of MXene layers and a plurality of MMT layers. The MXene and MMT nanosheets in the alternating layered structure are highly and regularly oriented along the plane direction, so that excellent anisotropic heat-conducting property can be effectively realized. As a heat diffuser of a high-performance electronic device, the film has more excellent cooling efficiency than a traditional commercial heat-conducting film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of thermally conductive composite materials, and in particular to an ultra-high anisotropic thermally conductive MXene film and a preparation method thereof. Background Art

[0002] With the rapid development of modern electronic devices towards miniaturization, high power and integration, the demand for materials with efficient thermal management capabilities is increasing. Anisotropic thermal conductive films have excellent controllable directional heat transfer capabilities. Their in-plane thermal conductivity is much higher than that of the out-of-plane direction. They can quickly conduct heat from the plane direction and protect the electronic components underneath from being affected. Therefore, they have attracted widespread attention from researchers (Adv. Funct. Mater. 2015, 25, 4664-4672). The anisotropy index is defined as the ratio of the in-plane thermal conductivity to the out-of-plane thermal conductivity, and is usually used to evaluate the anisotropic thermal conductivity of thermal conductive films. In order to achieve the preparation of high-performance anisotropic thermal conductive films, researchers have developed various specific structures to realize the anisotropic heat transport of phonons, including superlattices (Science 2004, 303, 989-990) and phononic crystals (Nature 2021, 597, 660-665). However, the preparation process of the above-mentioned anisotropic thermal conductive film is complicated, and the thickness of the obtained film is only at the nanometer level, which is difficult to be used in practical electronic devices. In addition, researchers have prepared thicker macroscopic anisotropic thermal conductive films by preparation methods such as layer-by-layer self-assembly, vacuum filtration, and blade coating. For example, a nanocellulose / reduced graphene oxide film was prepared by a layer-by-layer self-assembly method, and its anisotropy index was only 279 (Adv. Funct. Mater. 2022, 32, 2110782). In addition, the boron nitride / aramid nanofiber highly anisotropic thermal conductive film prepared by vacuum filtration has in-plane and out-of-plane thermal conductivities of 46.7 and 0.13 W / mK, respectively, and an anisotropy index of 372 (Adv. Mater. 2020, 32, 1906939). Despite certain research progress, the performance of macroscopic anisotropic thermal conductive films is still lower than required. Therefore, for the thermal management of high-performance electronic devices, it is urgent to design and develop anisotropic thermally conductive films with excellent anisotropic thermal conductivity. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides an ultra-high anisotropic thermal conductive MXene film. The ultra-high anisotropic thermal conductive MXene film is a MXene / MMT composite film, which is formed by alternating stacking of multiple MXene layers and multiple MMT layers, and has an anisotropy index of 259 to 707. As a heat diffuser for high-performance electronic devices, it has better cooling efficiency than traditional commercial thermal conductive films.

[0004] The present invention also provides a method for preparing the above-mentioned ultra-high anisotropic thermal conductive MXene film.

[0005] The present invention is achieved through the following technical solutions:

[0006] A super anisotropic thermal conductive MXene film, wherein the super anisotropic thermal conductive MXene film is a MXene / MMT composite film, which is formed by alternating stacking of multiple MXene layers and multiple MMT layers; wherein the MXene layers and the MMT layers are highly regularly oriented along the plane direction. The obtained super anisotropic thermal conductive MXene film has an anisotropy index of 259 to 707. As a heat diffuser for high-performance electronic devices, it has better cooling efficiency than traditional commercial thermal conductive films.

[0007] A method for preparing an ultra-high anisotropic thermal conductive MXene film comprises the following steps:

[0008] (1) Titanium carbide (Ti3C2T x MXene) sol coating to obtain a MXene layer, followed by drying to obtain a dry MXene layer;

[0009] (2) coating a montmorillonite (MMT) dispersion on the dried MXene layer to obtain an MMT layer, and then drying to obtain a dried MMT layer;

[0010] (3) Steps (1) and (2) are repeated alternately to obtain a MXene film with ultra-high anisotropic thermal conductivity. That is, the MMT layer is scraped on the MXene layer, and the MXene layer is scraped on the MMT layer. The ultra-high anisotropic thermal conductivity MXene film can be obtained by alternately scraping.

[0011] Furthermore, the step (3) further comprises a cross-linking treatment step, and the step (3) is specifically as follows:

[0012] (3) Repeating steps (1) and (2) alternately, and subjecting the obtained MXene / MMT composite film to a cross-linking treatment with a silane coupling agent to obtain an ultra-high anisotropic thermal conductive MXene film. The cross-linking treatment is to immerse the MXene / MMT composite film in a silane coupling agent solution for a certain period of time and then dry it. The introduction of the silane coupling agent enhances the interfacial interaction between the nanosheets.

[0013] More preferably, the silane coupling agent can be an epoxy silane coupling agent, a mercapto silane coupling agent, an olefin silane coupling agent, and an amino silane coupling agent. The silane coupling agents used in the embodiment of the present invention are (3-chloropropyl) triethoxysilane and (3,3,3-trifluoropropyl) trimethoxysilane. The immersion concentration (concentration of the silane coupling agent) is 5 mg / mL ~50 mg / mL, and the immersion time is 6~18 hours.

[0014] Among them, the thickness of the MXene layer is 200 nm~300 nm.

[0015] Among them, the thickness of the MMT layer is 50 nm~100 nm.

[0016] Wherein, in step (1) and step (2), the coating is carried out by a scraping method, wherein the scraping speed is 50 mm / s to 100 mm / s, and the scraping temperature is 40°C to 50°C. By adjusting the scraping speed and the scraping temperature, the MXene sol or MMT dispersion in step (3) is prepared by a scraping method to form a corresponding MXene layer or MMT layer; preferably, in step (4), the scraping speed is 50 mm / s to 100 mm / s (for example, the scraping speed is 50 mm / s, 60 mm / s, 80 mm / s, or 100 mm / s), and the scraping temperature is 40°C to 50°C (for example, the scraping temperature is 40°C, 43°C, 45°C, or 50°C); more preferably, the scraping speed is 50 mm / s, and the scraping temperature is 43°C.

[0017] Wherein, the concentration ratio of the MXene sol to the montmorillonite nanosheet dispersion is 1:1 to 4:1.

[0018] Wherein, the concentration of the MXene sol is 10 mg / mL~40 mg / mL;

[0019] Wherein, the concentration of montmorillonite nanosheet dispersion is 5 mg / mL~20 mg / mL.

[0020] Furthermore, the preparation process of the montmorillonite nanosheet dispersion is as follows: adding raw montmorillonite powder to deionized water, stirring evenly, and centrifuging to obtain the montmorillonite nanosheet dispersion. Specifically, adding raw MMT powder to deionized water, subjecting to 1 h of water bath ultrasound, 7 d of mechanical stirring, and centrifuging at 2800 rpm to obtain a MMT nanosheet dispersion with a concentration of 5 mg / mL to 20 mg / mL (for example, the concentration of the MMT nanosheet dispersion is 5 mg / mL, 10 mg / mL, 15 mg / mL, or 20 mg / mL).

[0021] Furthermore, the preparation process of the titanium carbide sol is as follows: the titanium carbide nanosheet dispersion is centrifuged to remove the supernatant, and the obtained precipitate is stirred and degassed to obtain the MXene sol. Specifically, titanium carbide (Ti3C2T x The MXene) nanosheet dispersion was centrifuged at 10000 rpm for 20 min, the supernatant was removed, and the obtained precipitate was subjected to 5 min 40W ultrasound, 5 min stirring, and 30 min degassing to obtain a MXene sol, and the concentration of the MXene sol was 10 mg / mL~40 mg / mL (for example, the concentration of the MXene sol is 10 mg / mL, 20 mg / mL, 30 mg / mL or 40 mg / mL).

[0022] Furthermore, the above Ti3C2T x MXene solution is prepared by in-situ hydrofluoric acid etching. The specific preparation process is as follows: the raw material MAX powder (Ti3AlC2) is slowly added to a solution containing mL hydrochloric acid (HCl) (9 M) and lithium fluoride (LiF), and stirred in a 50ºC water bath for 30 hours; the mixture after complete reaction is centrifuged, the upper liquid is poured out, and the mixture is repeatedly washed with deionized water 8 to 10 times until the pH exceeds 6, and the supernatant is poured out; the precipitate after centrifugation is dispersed in deionized water, and 7 mg / mL Ti3C2T is obtained after repeated oscillation and centrifugation. x MXene nanosheet dispersion, wherein the ratio of MAX powder, hydrochloric acid and lithium fluoride is 1(g):20(ml):1.6(g) to 1(g):20(ml):1.0(g).

[0023] Wherein, the concentration of the titanium carbide nanosheet dispersion is 5 mg / mL~10 mg / mL.

[0024] Principle of the invention: The present invention adopts Ti3C2T x MXene nanosheets and montmorillonite nanosheets are used as assembly primitives to prepare ultra-high anisotropic thermal conductivity MXene films through layer-by-layer scraping self-assembly process and interface cross-linking assembly. In the MXene / MMT composite film, the MXene nanosheets and MMT nanosheets are highly oriented along the plane, and the interface interaction between the nanosheets is enhanced by introducing silane coupling agents, achieving ultra-high anisotropic thermal conductivity, that is, high in-plane thermal conductivity while reducing the thermal conductivity in the out-of-plane direction. As a heat spreader for high-performance electronic devices, it has better cooling efficiency than traditional commercial thermal conductive films.

[0025] The advantages of the present invention compared with the prior art are:

[0026] (1) The present invention designs and prepares a MXene / MMT alternating layered structure through an alternating layer-by-layer self-assembly method, which is simple and easy to implement.

[0027] (2) The highly regular orientation of MXene and MMT nanosheets along the planar direction in the alternating layered structure of the present invention can effectively achieve excellent anisotropic thermal conductivity.

[0028] (3) The ultra-high anisotropic thermal conductive MXene film prepared by the present invention has better cooling efficiency as a heat diffuser for high-performance electronic devices than traditional commercial thermal conductive materials and currently reported thermal conductive materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The microstructure, orientation and interface interaction of the ultra-high anisotropic thermal conductive MXene film prepared in Example 5. a is a transmission electron microscope photo of the cross section of the ultra-high anisotropic thermal conductive MXene film; b is a TEM photo of the cross-sectional element distribution of the ultra-high anisotropic thermal conductive MXene film, in which titanium and silicon elements are distributed in alternating layers; c is a wide-angle X-ray scattering (WAXS) spectrum of the comparative example (MXene film) and the MXene / MMT composite film prepared in Example 5 and its corresponding 002 peak azimuth scanning curve; d is an X-ray photoelectron energy spectrum of Ti 2p in the MXene film and the MXene / MMT composite film.

[0030] Figure 2 The anisotropic thermal conductivity of the ultra-high anisotropic thermal conductive MXene film prepared in Example 5 and the MXene film prepared in the comparative example. a is the in-plane and out-of-plane thermal conductivity of the MXene film and the MXene / MMT composite film; b is the anisotropy index of the MXene film and the MXene / MMT composite film.

[0031] Figure 3 This is a demonstration of the application of the ultra-high anisotropic thermal conductive MXene film prepared in Example 5. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0033] Unless otherwise specified, the materials used in the present invention can be obtained commercially.

[0034] In the following examples of the present invention, some raw materials and preparation equipment are as follows:

[0035] Ti3AlC2 MAX (purity: 98%, 400 mesh, Jilin Yiyi Technology Co., Ltd.);

[0036] Lithium fluoride (purity: 98%, Aladdin);

[0037] Hydrochloric acid (purity: 36~38%, Sinopharm Chemical Reagent);

[0038] Montmorillonite (Beijing Yiwei Special Chemical Technology Development Co., Ltd.);

[0039] The orientation degree of the ultra-high anisotropic thermal conductive MXene film was tested using a wide-angle X-ray diffractometer (Xenocs Xeuss SAXS / WAXS, Cu-Kα X-ray beam);

[0040] The cross-sectional morphology of the MXene / MMT composite film was observed using a focused ion beam scanning electron microscope (FIB, Helios G4 CX, FEI Company, USA) and a transmission electron microscope (Titan Themis G3, FEI Company, USA);

[0041] The molecular structure and chemical composition of MXene film and MXene / MMT film were tested using an X-ray photoelectron spectrometer (ESCALAB 250Xi, Thermo Fisher Scientific, USA).

[0042] The in-plane and out-of-plane thermal conductivity of MXene films and MXene / MMT composite films were tested using a laser thermal conductivity meter (LFA467, NETZSCH, Germany).

[0043] Thermal imaging photographs of MXene films and MXene / MMT films as heat sinks for cooling electronic devices were recorded using an infrared thermal imager (FOTRIC 228s, Shanghai Thermal Imaging Technology Co., Ltd.).

[0044] Example 1

[0045] Preparation:

[0046] (1) Preparation of Ti3C2T x MXene nanosheet dispersion.

[0047] 3 g of raw material Ti3AlC2 MAX powder was slowly added to a solution containing 60 mL of hydrochloric acid (HCl) (9 M) and 4.8 g of lithium fluoride (LiF), and stirred in a water bath at 50°C for 30 hours; the mixture after complete reaction was centrifuged, the upper liquid was discarded, and the mixture was repeatedly washed with deionized water for 8-10 times until the pH exceeded 6, and the supernatant was discarded; the precipitate after centrifugation was dispersed in deionized water, and 7 mg mL -1 Ti3C2T x MXene nanosheet dispersion.

[0048] (2) Preparation of MMT dispersion.

[0049] 15 g of raw MMT powder was added to 500 mL of deionized water, and the concentration of MMT nanosheet dispersion was obtained by 1 h of water bath ultrasound, 7 d of mechanical stirring and 2800 rpm centrifugal separation. The concentration of the MMT nanosheet dispersion was 10 mg / mL.

[0050] (3) Preparation of MXene sol.

[0051] Titanium carbide (Ti3C2T x The MXene) nanosheet dispersion was centrifuged at 10000 rpm for 20 min, the supernatant was removed, and the precipitate was subjected to 5 min 40 W ultrasound, 5 min stirring and 30 min degassing to obtain MXene sol. The concentration of MXene sol was 20 mg / mL.

[0052] A method for preparing an ultra-high anisotropic thermal conductive MXene film comprises the following steps:

[0053] (1) The MXene sol was scraped at a scraping speed of 50 mm / s, a scraping temperature of 40 °C, and a scraper height of 100 μm, and dried to obtain a dry MXene layer;

[0054] (2) Then, the MMT dispersion was scraped according to the same parameters to obtain a dry MXene layer / MMT layer.

[0055] (3) The above steps are then repeated, and the MXene layer and the MMT layer are alternately scraped and coated to obtain a MXene / MMT composite film, i.e., an ultra-high anisotropic thermal conductive MXene film.

[0056] Example 2

[0057] The raw materials and preparation process of this embodiment are the same as those of Example 1.

[0058] The difference is that the concentration of MXene sol is 10 mg / mL, and the concentration of MMT nanosheet dispersion is 5 mg / mL. The scraping speed is 60 mm / s, and the scraping temperature is 43 °C.

[0059] Example 3

[0060] The raw materials and preparation process of this embodiment are the same as those of Example 1.

[0061] The difference is that the concentration of MXene sol is 30 mg / mL, and the concentration of MMT nanosheet dispersion is 15 mg / mL. The scraping speed is 80 mm / s and the scraping temperature is 45 °C.

[0062] Example 4

[0063] The raw materials and preparation process of this embodiment are the same as those of Example 1.

[0064] The difference is that the concentration of MXene sol is 40 mg / mL, and the concentration of MMT nanosheet dispersion is 20 mg / mL. The scraping speed is 100 mm / s, and the scraping temperature is 50 °C.

[0065] Example 5

[0066] Preparation:

[0067] (1) Preparation of Ti3C2T x MXene nanosheet dispersion.

[0068] 3 g of raw material Ti3AlC2 MAX powder was slowly added to a solution containing 60 mL of hydrochloric acid (HCl) (9 M) and 4.8 g of lithium fluoride (LiF), and stirred in a water bath at 50°C for 30 hours; the mixture after complete reaction was centrifuged, the upper liquid was discarded, and the mixture was repeatedly washed with deionized water for 8-10 times until the pH exceeded 6, and the supernatant was discarded; the precipitate after centrifugation was dispersed in deionized water, and 7 mg mL -1 Ti3C2T x MXene nanosheet dispersion.

[0069] (2) Preparation of MMT dispersion.

[0070] 15 g of raw MMT powder was added to 500 mL of deionized water, and the concentration of MMT nanosheet dispersion was obtained by 1 h of water bath ultrasound, 7 d of mechanical stirring and 2800 rpm centrifugal separation. The concentration of the MMT nanosheet dispersion was 10 mg / mL.

[0071] (3) Preparation of MXene sol.

[0072] Titanium carbide (Ti3C2Tx The MXene) nanosheet dispersion was centrifuged at 10000 rpm for 20 min, the supernatant was removed, and the precipitate was subjected to 5 min 40 W ultrasound, 5 min stirring and 30 min degassing to obtain MXene sol. The concentration of MXene sol was 20 mg / mL.

[0073] A method for preparing an ultra-high anisotropic thermal conductive MXene film comprises the following steps:

[0074] (1) Scrape the MXene sol at a scraping speed of 50 mm / s to 100 mm / s, a scraping temperature of 40 °C to 50 °C, and a scraper height of 100 μm, and dry to obtain a dry MXene layer;

[0075] (2) Then, the MMT dispersion is coated according to the same parameters to obtain a dry MXene layer / MMT layer;

[0076] (3) Then repeat the above steps, alternately scraping the MXene layer and the MMT layer to obtain a MXene / MMT composite film;

[0077] (4) The MXene / MMT composite film obtained in step (3) is subjected to covalent cross-linking treatment with a silane coupling agent to obtain an ultra-high anisotropic thermal conductive MXene film. The silane coupling agent in this embodiment is (3-chloropropyl) triethoxysilane (CPTES), the immersion concentration is 10 mg / mL, and the immersion time is 12 hours. It is denoted as MXene / MMT in the accompanying drawings.

[0078] Comparative Example

[0079] In this comparative example, pure MXene film was prepared by layer-by-layer self-assembly process. Specifically, titanium carbide (Ti3C2T x After the dispersion of MXene nanosheets was centrifuged at 10,000 rpm for 20 min, the supernatant was removed and the precipitate was subjected to 5 min 40 W ultrasound, 5 min stirring and 30 min degassing to obtain MXene sol, with a MXene sol concentration of 20 mg / mL. The MXene sol was scraped at a scraping speed of 50 mm / s~100 mm / s, a scraping temperature of 40 ℃~50 ℃, and a scraper height of 100 μm, and then the above steps were repeated to obtain a pure MXene film. It is marked as MXene in the attached figure.

[0080] like Figure 1 a and Figure 1 As shown in (b), MXene and MMT layers are distributed alternately, and the MXene nanosheet structure is arranged regularly.

[0081] like Figure 1 As shown in Figure c, the MXene / MMT composite film prepared by the layer-by-layer self-assembly process exhibits a high orientation degree of 0.972, which is higher than that of the pure MXene film. Figure 1 As shown in Figure d, a new Ti-O-Si characteristic peak appeared at 460 eV in the MXene / MMT composite film after covalent cross-linking with a silane coupling agent, which fully demonstrated that the silane coupling agent successfully covalently cross-linked with MXene and MMT.

[0082] like Figure 2 As shown in a, the in-plane and out-of-plane thermal conductivity of the ultra-high anisotropic thermal conductive MXene / MMT film are 63.4 and 0.09 W / mK, respectively, and the in-plane thermal conductivity is much higher than that of the pure MXene film. Figure 2 As shown in (b), the anisotropy index of the MXene / MMT composite film is as high as 707, which is higher than that of the pure MXene film (anisotropy index is 237) and much higher than that of the polyimide film currently used commercially (whose anisotropy index is about 15).

[0083] like Figure 3 As shown in a, the MXene / MMT composite film can reduce the surface temperature of the ceramic heating plate that is being electrically heated to 103.7°C. As a comparison, the surface temperature of the ceramic heating plate without the MXene / MMT composite film is 178.4°C. Figure 3 As shown in (b), the cooling efficiency of the MXene / MMT composite film (i.e., the ratio of the reduced temperature difference to the original temperature) far exceeds that of commercial thermal conductive materials and currently reported anisotropic thermal conductive films.

[0084] Example 6

[0085] The preparation process of this embodiment is the same as that of embodiment 5.

[0086] The difference is that the concentration of the silane coupling agent is 5 mg / mL and the immersion time is 18 hours.

[0087] Example 7

[0088] The preparation process of this embodiment is the same as that of embodiment 5.

[0089] The difference is that the concentration of the silane coupling agent is 20 mg / mL.

[0090] Example 8

[0091] The preparation process of this embodiment is the same as that of embodiment 5.

[0092] The difference is that the concentration of the silane coupling agent is 50 mg / mL.

[0093] Example 9

[0094] The raw materials and preparation process of this embodiment are the same as those of Example 1.

[0095] The difference is that the concentration of MXene sol is 20 mg / mL, and the concentration of MMT nanosheet dispersion is 5 mg / mL. The scraping speed is 50 mm / s, and the scraping temperature is 43 °C.

[0096] Example 10

[0097] The raw materials and preparation process of this embodiment are the same as those of Example 5.

[0098] The difference is that the silane coupling agent is (3,3,3-trifluoropropyl)trimethoxysilane and the immersion time is 6 hours.

[0099] Embodiment 11

[0100] The raw materials and preparation process of this embodiment are the same as those of Example 1.

[0101] The difference is that the concentration of MXene sol is 10 mg / mL, and the concentration of MMT nanosheet dispersion is 5 mg / mL. The scraping speed is 60 mm / s, and the scraping temperature is 43 °C.

[0102] The test results of the in-plane thermal conductivity, out-of-plane thermal conductivity and anisotropy index of Examples 1 to 11 and the comparative example are shown in Table 1.

[0103] Table 1

[0104] It can be seen from Table 1 that the anisotropy index of the ultra-high anisotropic thermal conductive MXene film of the present invention is significantly higher than that of the comparative example; and the effect of using a silane coupling agent is better.

[0105] It should be noted that, according to the above-mentioned embodiments of the present invention, those skilled in the art can fully implement the entire scope of claim 1 and the appendant rights of the present invention, and the implementation process and method are the same as the above-mentioned embodiments; and the parts not elaborated in detail in the present invention belong to the well-known technology in the field.

[0106] The above descriptions are only some specific implementation methods of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any person familiar with the art within the technical scope disclosed in the present invention should be covered within the protection scope of the present invention.

Claims

1. An ultra-high anisotropic thermal conductive MXene film, characterized in that: The ultra-high anisotropic thermal conductive MXene film is a MXene / MMT composite film, which is formed by alternatingly stacking multiple MXene layers and multiple MMT layers.

2. The method for preparing the ultra-high anisotropic thermal conductive MXene film according to claim 1, characterized in that: The following steps are involved: (1) coating the MXene sol to obtain a MXene layer, and then drying to obtain a dry MXene layer; (2) applying a montmorillonite dispersion on the dried MXene layer to obtain an MMT layer, followed by drying; (3) By alternately repeating steps (1) and (2), an ultra-high anisotropic thermal conductive MXene film can be obtained.

3. The preparation method according to claim 2, characterized in that: The step (3) further includes a cross-linking treatment step, and the step (3) specifically comprises: (3) Step (1) and step (2) are repeated alternately, and the obtained MXene / MMT composite film is cross-linked with a silane coupling agent to obtain an ultra-high anisotropic thermal conductive MXene film.

4. The preparation method according to claim 3, characterized in that: The immersion concentration is 5 mg / mL to 50 mg / mL, and the immersion time is 6 to 18 hours.

5. The preparation method according to claim 2, characterized in that: The thickness of the MXene layer is 200 nm~300 nm; And / or, the MMT layer has a thickness of 50 nm to 100 nm.

6. The preparation method according to claim 2, characterized in that: Step (1) and step (2) are coated by a scraping method, wherein the scraping speed is 50 mm / s to 100 mm / s and the scraping temperature is 40°C to 50°C.

7. The preparation method according to claim 2, characterized in that: The concentration ratio of the MXene sol to the montmorillonite nanosheet dispersion is 1:1 to 4:

1.

8. The preparation method according to claim 2, characterized in that: The concentration of the MXene sol is 10 mg / mL to 40 mg / mL; And / or, the concentration of the montmorillonite nanosheet dispersion is 5 mg / mL to 20 mg / mL.

9. The preparation method according to claim 2, characterized in that: The preparation process of the montmorillonite nanosheet dispersion is as follows: adding raw montmorillonite powder into deionized water, stirring evenly, and centrifuging to obtain the montmorillonite nanosheet dispersion.

10. The preparation method according to claim 2, characterized in that: The preparation process of the titanium carbide sol is as follows: the titanium carbide nanosheet dispersion is centrifuged to remove the supernatant, and the obtained precipitate is stirred and degassed to obtain the MXene sol.

Citation Information

Cited By

  • Anisotropic heat-conducting flame-retardant battery cell spacer and preparation method thereof

    CN121601876A

  • Anisotropic heat-conducting flame-retardant cell spacer and preparation method thereof

    CN121601876B

  • Heat dissipation-flame retardant integrated flexible multifunctional composite film as well as preparation method and application thereof

    CN122301526A